Performance and Carcass Composition of Male Ma Ducks Given Bay Leaf Solution in Drinking Water - Anggraeni Anggraeni; Ristika Handarini; Agung Puji Haryanto (Indonesian Journal of Applied Research (IJAR), 2020)
Bay leaves contain flavonoid active compounds including quercetine and fluoretine having antioxidative and antimicrobial properties. Bay leaves can be given as feed additive to improve body metabolism in animals. This study was aimed at assessing the effects of the inclusion of bay leaf solution in drinking water on the performance and carcass quality of male MA ducks. Seventy-two male one-day-old MA ducks were allocated into battery cages (50 cm length, 50 cm width, 78 cm height). The ducks were fed commercial rations containing 21-23% CP and 2820-2920 Kcal/kg ME and given drinking water containing bay leaf solution (LDS). A completely randomized design with 3 treatments and 6 replicates of 4 ducks each was used. Treatments consisted of drinking water containing no LDS (R0), drinking water containing 4% LDS (R1), and drinking water containing 8% LDS (R2). Measurements were taken on production performance and percentages of carcass parts. Results showed that th einclusion of LDS in drinking water gave significant effects (P<0.05) on body weight gain but not (P>0.05) on all carcass composition parameters. It was concluded that the inclusion of LDS in drinking water up to 8% resulted in a mean body weight gain of 194.88±10.88 g/head/day but did not affect the percentages of carcass and its parts including breast, wing, and thigh. It was recommended that LDS be included by up to 8% in drinking water of male MA ducks for optimal body weight gain.